Gender Specific Correlation between Lip Print, Fingerprint and Blood Groups among Adults aged 20-30 Years attending a Tertiary Health Care Centre - Ghimire, Pratikshya; Ghimire, Sima; Khanal, Adarsha; Khapung, Anju (Nepal Medical College Journal, 2022)
A cross-sectional study was conducted to determine gender specific correlation between lip print, finger print and blood group among 120 adult clinical cases in a tertiary hospital in Kathmandu. Lip prints were collected using lipstick and cellophane sheet. Thumb print was collected using commercially available ink pad and white paper and analyzed using hand held magnifying lens. Blood group was noted at the time of recording lip and thumb print. A statistically significant association of gender with fingerprint (p=<0.001) and lip print (p=0.001) was found. A strong co-existing relation have been found between gender and the loop fingerprint-lip print type I’- blood group O and arch fingerprint–lip print type I’– blood group ‘O’.